THE INFLUENCE OF DIGITAL LEADERSHIP STYLE, WORK MOTIVATION ON EMPLOYEE PERFORMANCE : A MEDIATION OF WORK DISCIPLINE - Ismarsanto, Falya Ikhlimarisqi; Kirana, Kusuma Chandra; Kusuma, Nala Tri (International Conference on Humanity Education and Society (ICHES), 2024)
This study aims to examine the effect of digital leadership style and work motivation on employee performance through work discipline as a mediating variable. This research is quantitative in nature using Non-Probability sampling technique, with a sample of 50 employees who have worked for more than 2 years at Super dazzle Gejayan. The results showed that digital leadership style has a positive and significant effect on work discipline, work motivation has a positive and significant effect on work discipline, work discipline has a positive and significant effect on employee performance, leadership style has a positive and significant effect on employee performance, work motivation has a positive and significant effect on employee performance, and work discipline has a positive and significant effect as a mediator of work motivation on employee performance. The implications of this research are, if work discipline is improved, it will improve employee performance, for further research, it can add the dependent variable work environment to find out whether the work environment will affect employee performance and can also use compensation variables.